Biweekly Doxorubicin/Ketoconazole as Second-Line Treatment in Docetaxel-Resistant, Hormone-Refractory Prostate Cancer - Lainakis, G.; Nikos, A.; Gerassimos, A.; Michael, C.; Iraklis, M.; Konstantinos, L.; Ioannis, V.; Harilaos, K.; Dimopoulos, M.A.; Bamias, A. (Urology, 2008)
Objectives: Docetaxel is an effective first-line treatment for hormone-refractory prostate cancer. Nevertheless, the prognosis subsequent to progression after first-line therapy is poor and no second-line treatment has been established. Methods: A total of 34 patients with androgen-independent prostate cancer received doxorubicin, 30 mg/m2, every 2 weeks and ketoconazole daily, 400 mg orally every 8 hours. All patients had been treated with docetaxel and had disease progression within 6 months after completion of first-line treatment. Results: Of the 32 evaluable patients, 13 (43.7%, 95% confidence interval [CI] 26.3% to 62.3%) had a prostate-specific antigen (PSA) response, and 4 (28%, 95% CI 8.4% to 58.1%) of 14 patients with measurable disease had a response to therapy. The median time to progression (TTP) was 3.9 months (95% CI 2.0 to 5.9), and the median overall survival (OS) was 13 months (95% CI 8.7 to 17.3). Toxicity was mild, with only 4 cases of nonhematologic grade 3 or 4 toxicity. The most frequent toxicity was nail changes (33 of 34 patients), which was mainly grade 1 (30 cases). Conclusions: The combination of biweekly doxorubicin and ketoconazole is an effective, well-tolerated, second-line therapy for hormone-refractory prostate cancer. © 2008 Elsevier Inc. All rights reserved.